Tinjauan Tentang Penggunaan Mobil Pick-Up Sebagai Alat Pengangkutan Penumpang Antar Kota-Kabupaten Kupang Berdasarkan Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan - Samuel Touselak; Deby F Ng Fallo; Adrianus Djara Dima (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study examines the gap between the normative regulations governing intercity and interdistrict passenger transportation, as stipulated in Law Number 22 of 2009 concerning Road Traffic and Transportation, and the common practice in Kupang East Nusa Tenggara, where pick-up trucks are used as a means of passenger transportation. The study aims to assess how these regulations are implemented and to analyze the social, economic, and safety impacts arising from the use of this mode of transportation. This research employs an empirical legal research method with a qualitative descriptive approach, conducted through interviews with officials from the Transportation Agency, pick-up truck drivers, and passengers. The findings reveal that although pick-up trucks are officially classified as goods vehicles and are prohibited from transporting passengers, the prohibition has not been effectively enforced in practice. This situation is caused by the limited availability of public transportation, challenging geographical conditions, and the economic circumstances of the community. The impacts of this condition include the community’s social dependence on pick-up trucks, unfair business competition, and safety risks for passengers. Therefore, more adaptive and equitable transportation policies are needed.